The Sarcoglycan complex is expressed in the cerebrovascular system and is specifically regulated by astroglial Cx30 channels - Boulay, Anne-Cécile; Saubaméa, Bruno; Cisternino, Salvatore; Mignon, Virginie; Mazeraud, Aurélien; Jourdren, Laurent; Blugeon, Corinne; Cohen-Salmon, Martine (Frontiers in Cellular Neuroscience, 2015)
Astrocytes, the most prominent glial cell type in the brain, send specialized processes called endfeet, around blood vessels and express a large molecular repertoire regulating the cerebrovascular system physiology. One of the most striking properties of astrocyte endfeet is their enrichment in gap junction protein Connexin 43 and 30 (Cx43 and Cx30) allowing in particular for direct intercellular trafficking of ions and small signaling molecules through perivascular astroglial networks. In this study, we addressed the specific role of Cx30 at the gliovascular interface. Using an inactivation mouse model for Cx30 (Cx30Δ/Δ), we showed that absence of Cx30 does not affect blood-brain barrier (BBB) organization and permeability. However, it results in the cerebrovascular fraction, in a strong upregulation of Sgcg encoding γ-Sarcoglycan (SG), a member of the Dystrophin-associated protein complex (DAPC) connecting cytoskeleton and the extracellular matrix. The same molecular event occurs in Cx30T5M/T5M mutated mice, where Cx30 channels are closed, demonstrating that Sgcg regulation relied on Cx30 channel functions. We further characterized the expression of other Sarcoglycan complex (SGC) molecules in the cerebrovascular system and showed the presence of α-, β-, δ-, γ-, ε- and ζ- SG, as well as Sarcospan. Their expression was however not modified in Cx30Δ/Δ. These results suggest that a full SGC might be present in the cerebrovascular system, and that expression of one of its member, γ-Sarcoglycan, depends on Cx30 channels. As described in skeletal muscles, the SGC may contribute to membrane stabilization and signal transduction in the cerebrovascular system, which may therefore be regulated by Cx30 channel-mediated functions.